Families with high-risk characteristics and diagnoses of attention-deficit/hyperactivity disorder, autism spectrum disorder, intellectual disability, and learning disability in children: A national birth cohort study - Lung, For-Wey; Chen, Po-Fei; Shen, Li-Jong; Shu, Bih-Ching (Frontiers in Psychology, 2022)
Background: A national birth cohort study was used to investigate whether high-risk family factors at 1.5-years-old can increase the risk of attention-deficit/hyperactivity disorder (ADHD) diagnosis when children reach 5.5 years. The pathway relationship of high-risk family factors, children’s developmental conditions, risk of autism spectrum disorder (ASD), and diagnosis of intellectual disability (ID), learning disability (LD), and ASD was also investigated. Methods: The 1.5-, 3- and 5.5-year-old Taiwan Birth Cohort Study dataset was used (N=19,185). High-risk familial factor was measured using five questions of: parents are currently unmarried, unemployed, do not have any social insurance, perceive a ‘very heavy’ economic childcare burden, or at least one of the parents has a disability certification. Developmental conditions were assessed using the Taiwan Birth Cohort Study – Developmental Instrument, and ASD risk was measured using the Modified Checklist of Autism in Toddlers. ADHD, ID, LD, and ASD diagnoses were collected at age 5.5 years. Odds ratio model investigated whether children from families with high-risk factors at 1.5-years were at increased risk of ADHD, ID, LD, or ASD diagnosis at 5.5-years, compared to those children from families without such risks. Structural equation modeling investigated the logistic regression pathway relationship of high-risk familial characteristics, children’s developmental conditions, autism screening and diagnosis. Results: In the national birth cohort dataset of 19,185 children, 2070 (10.8%) met at least one of the high-risk familial factors. Children who met one high-risk familial factor had 1.21-fold increased risk for ADHD diagnosis, 1.36-fold increased risk for LD diagnosis, and 1.80-fold increased risk for ASD diagnosis, compared to children from families without risks. High-risk familial factors directly increased the risk of ADHD and ID diagnosis, and indirectly increased the risk of ADHD, ID, LD, and ASD diagnosis through the mediating factor of children’s development. Conclusions: Children who met more high-risk familial characteristics were at higher risk of ADHD, ID, LD and ASD diagnosis. Development at 3 years was predictive of diagnosis at 5.5 years. Thus, developmental screening at age 3 is vital for interventions. Preventive family-focused and/or child-rearing services for at-risk families is important for improving outcomes for these children and their families.